Simplified Calculation of Counteraction EMF in the Multimotor PWR Converter Cascade Drive - Kepalas, P. V.; Ramonas, S. C. (Elektronika ir Elektrotechnika, 1999)
The method permitting to estimate changes of the inverter counteraction EMF in the multimotor pulse width regulated (PWR) converter cascade drive is presented. The obtained mathematical expressions permit to achieve most convenient way for creating speed-torque characteristics of the multimotor PWR converter cascade drive.